The Influence Of Product Quality, Price, Brand Image And Promotion On The Purchase Decision Of Xiaomi Smartphone Products In Depok City - Faramita Dwitama (Publisher Cv. Inara, 2021)
Technological developments and a lot of competitors in the smartphone industry make the competition tighter so that it triggers consumers to be more picky before deciding to make a purchase. Xiaomi is one of the manufacturers engaged in the production of smartphones which is well known in Indonesia. The purpose of this study is to determine whether product quality, price, brand image, and promotion can partially and simultaneously influence purchasing decisions for Xiaomi smartphones in Depok. This study uses quantitative primary data in the form of a questionnaire with a research sample of 100 respondents. The analytical tools used are validity test, reliability test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, normality test, coefficient of determination, t test and f test assisted by SPSS version 25 software. The results of this study are product quality, price , brand image, and promotion have a significant influence on purchasing decisions for Xiaomi smartphones in Depok city, either partially or simultaneously.